Solution of the plane contact problem between a finite-thickness laterally graded solid and a rigid stamp of an arbitrary tip-profile - Arslan, O. (Archives of Mechanics, 2019)
A singular integral equation (SIE) approach and a finite element method are developed for the solution of the frictional sliding contact problem between a finite-thickness laterally graded solid and a rigid stamp of an arbitrary tip-shape considering the plane strain assumption. An exponential shear modulus variation is introduced through the lateral direction. The field variables are obtained applying the Fourier transformation techniques on the governing partial differential equations. A surface displacement gradient is then utilized to derive a SIE of the second kind. A numerical solution of the SIE is performed by using a collation method and the Gauss quadrature integration techniques for the flat, triangular and circular stamp profiles. Finite element analyses (FEA) of the same contact problems are also performed upon selection of the augmented Lagrange contact-solver in ANSYS. For the incomplete (triangular and circular) stamp problems, an iterative algorithm is developed in order to obtain practically computational solutions for any desired contact lengths. Successful convergence of the SIE results and excellent consistency between the SIE and FEA results are attained, that indicate the reliability of both methods. The change in the thickness is shown to alter the contact behavior of the laterally graded solid significantly.